2009
DOI: 10.4039/n09-029
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in Ephedrus persicae (Hymenoptera: Braconidae: Aphidiinae): intraspecific variation in size and shape

Abstract: Sexual dimorphism in size and shape has been studied in a wide range of organisms, but intraspecific variation in sexual dimorphism remains largely unexplored. In many parasitoid species the diversity of morphological-variation patterns within species is complicated by host effects. It is not known whether the magnitude and direction of sexual size dimorphism can be affected by the developmental environment (i.e., different host species). In this study we explored patterns of sexual dimorphism in size and shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Besides temperature, environmental factors related to nutrition levels and/or quality influence organ size and shape. For instance, in the wasp Ephedrus persicae (Froggatt, 1904) that parasitizes aphids, wing size and shape depends on the type of host (Bogdanović et al, 2009). Different density regimes, inducing competition for nutrition levels, clearly affected wing size in all three studied species, a common trend previously observed in D. melanogaster (Bitner-Mathé and Klaczko, 1999;Siomava et al, 2016) and in C. capitata and M. domestica (Siomava et al, 2016).…”
Section: Plasticity In Response To Rearing Densitysupporting
confidence: 55%
“…Besides temperature, environmental factors related to nutrition levels and/or quality influence organ size and shape. For instance, in the wasp Ephedrus persicae (Froggatt, 1904) that parasitizes aphids, wing size and shape depends on the type of host (Bogdanović et al, 2009). Different density regimes, inducing competition for nutrition levels, clearly affected wing size in all three studied species, a common trend previously observed in D. melanogaster (Bitner-Mathé and Klaczko, 1999;Siomava et al, 2016) and in C. capitata and M. domestica (Siomava et al, 2016).…”
Section: Plasticity In Response To Rearing Densitysupporting
confidence: 55%
“…Our interspecific shape analysis revealed a clear sexual shape dimorphism which was most pronounced for C. capitata (Fig. 1B, Table 1) (see also (Pretorius, 2005; Bogdanović et al, 2009; Camargo et al, 2015)). The extreme sexual shape dimorphism in C. capitata likely explains the significant interaction between species and sex (Table 1).…”
Section: Resultsmentioning
confidence: 73%
“…Wing morphology and wing shape have great adaptive significance and could be related to varying ecological roles as well as to the physiological constraints of flight (e.g., Berwaerts et al 2002). Our earlier analysis of the variation in sexual dimorphism in wing shape among E. persicae biotypes (Mitrovski Bogdanović et al 2009) also revealed that the level and pattern of sexual dimorphism in wing size and wing shape differed among the biotypes, indicating a high level of morphological variation in wing shape within E. persicae. Diversification in body shape, or the shape of any particular morphological structure, may result from allometric shape changes and from alterations in shape unrelated to size (Bookstein 1991;Klingenberg 1996).…”
Section: Discussionmentioning
confidence: 90%